The Impact of Tourism on the Socio-Economic Development of Volyn Region - BEZSMERTNIUK, Taras; MELNIICHUK, Mykhailo; HORBACH, Liudmyla; HORBACH, Victoriia (Journal of Environmental Management and Tourism, 2022)
The purpose of the article is assess ing the impact of the tourism industry on the socio-economic development of Volyn region. The following methods were used to conduct an objective and thorough study: analysis and synthesis (to determine the sequence of the study); deduction and induction ( to choose a research strategy); systematization (to formulate the conclusions of the study); structural and logical generalization (to build a logical model of the research process); statistical (in the formation and processing of statistical information base); SWOT-analysis ( to estimate the tourist potential of the Volyn region). The possibilities of development of tourism in the region are determined, the influence of tourist activities on other sectors of the economy and the socio-economic effect from the organization of tourist activities in the region . The dynamics of tourist flows in the Volyn region has been analyzed and their role in the economic growth of the region has been assessed. Separate indicators of tourism demand and tourist proposal in the structure of economic region activity are investigated, which the analysis of the dynamics give grounds to assert both positive and negative trends in the development of a local tourist market . As part of the overall positive increase in demand, the development of supply should take place by improving quality and offers. The role and place of tourism enterprises in ensuring the economic growth of the region are clarified. It is established that the contribution of tourism infrastructure enterprises of the region to the local budget is insignificant. The main problems the functioning of the tourism industry are revealed and the directions the intensification of local authorities are outlined to ensure economic growth of the tourism industry. The development of the tourist industry of the Volyn region and the development the regional market of tourist services will positively affect the socio-economic situation of both the region and the state as a whole.